Ocena potomstwa buka zwyczajnego (Fagus sylvatica L.) w początkowych latach wzrostu - Banach, Jacek; Kubacki, Kamil; Skrzyszewska, Kinga; Smętek, Mateusz (Leśne Prace Badawcze, 2016)
This research was carried out on two experimental plots located in the Rymanów and Nawojowa forest districts. In the second and fifth year after planting, at three and six years of age respectively, survival and height of 25 beech progenies of selected stands were measured. Furthermore, we show the effect of beech origin and growth environment (significant ‘provenance × block’ and ‘provenance × test plot’ interactions). Beeches from both experimental plots differed significantly in growth and survival and this difference increased with tree age. The highest provenance heritability was obtained for the tree height after two years of growth in Rymanów. In Nawojowa, the heritability of beech survival reached zero after five years of growth. An evaluation of the stability of beech provenances (genotypes) in terms of survival and height under the habitat conditions of our experimental plots was done using the Finlay and Wilkinson method. The beech provenances of 469–Nawojowa and 452–Lesko (regional standard) were included as a stable basis for reference. A high degree of stability and high average values for the characteristics investigated indicate high progeny quality within these stands.